Semi-automatic parallel parking system. - Farrita, Nur Erniwati; Jaafar, Haslina; Mohd Sidek, Mohd Hasimi; Ahmad, Siti Anom
This project is to develop a low cost semi-automatic system specifically for parallel parking system. The system will guide driver to manoeuvre their car for parallel parking via graphical LCD operated by microcontroller and ultrasonic sensors. Rotary encoder is also used to provide real time feedback to the system to calculate and estimate the trajectory of the car when parking. The main function of this semi-automatic parking system is it can park towards side parking lot with the guidance of the sensors and encoder. The microcontroller is used to sequence the movement of the car by control it using ultrasonic sensor and encoder. With semi-automatic parallel parking system it can be useful to help the driver do the side parking. With this project it can reduce the risk of an accident occurs during the side parking. So it can avoid the damage and the loss of the car.